Mononeuropathy of the maxillary nerve branches associated with COVID-19 - Gaujac, Cristiano; Takeshita, Wilton Mitsunari; Gaujac, Danielle Pereira; Pedron, Irineu Gregnanin; Shinohara, Elio Hitoshi (ARCHIVES OF HEALTH INVESTIGATION, 2021)
This clinical note describes a case report where the patient notices that one of the symptoms suffered during COVID-19 infection is a mononeuropathy of the branches of the maxillary nerve, reviewing in the literature the findings of the affinity of the coronavirus to nerve fibers.